PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH DASAR INPRES SEIN ARAK KABUPATEN MALAKA - Bria, Bonefantura Jemy; Seuk, Marselina; Malli, Emanuel Je’e (Pastoralia Jurnal Penelitian Dosen, 2023)
This research uses quantitative methods with a rational-empirical approach, starting with identifying problems which are then studied theoretically before being analyzed empirically. Data collection was carried out through questionnaires and document studies, while data analysis used descriptive and inferential statistical techniques. The results of descriptive statistical analysis show that the achievement of the teacher performance variable indicator is 54.22% and the principal leadership variable is 56.51%, these two variables are categorized as quite good. Inferential analysis shows the significance of the principal leadership variable on teacher performance, with a significant beta value. The coefficient of determination confirms the contribution of the principal leadership variable of 43.8% to teacher performance, while the remainder is influenced by other factors. These findings indicate the leadership role of the principal in improving teacher performance at Inpres Sein Arak Elementary School, but also indicate the existence of other factors that also influence teacher performance.